The use of space images for solving problems of monitoring of forest - Шумаков, Федор Терентьевич; Толстохатько, Виктор Антонович; Тарнопильская, Надежда Петровна (Eastern-European Journal of Enterprise Technologies, 2012)
The method of analysis of dynamics of forest development by the images that are obtained by remote sensing of Earth from various satellites during different periods is suggested